EFEITO DE 8 SEMANAS DE TREINAMENTO FUNCIONAL EM IDOSAS - Neto, Antônio Antunes Beserra; Almeida, Francinei Herlon Jesus de; Leite, Italo Lagoa; Neves, Jéssica dos Santos; Cavalcante, Joás Dias de Áraujo (Seminário Transdisciplinar da Saúde, 2018)
>>> ver pdf